Conference organization - (:unkn) unknown (My University, 2018)
Deliverable (D) 4.8: Conference organization, documents all aspects related to the final symposium preparation and implementation, as a closing act of the Phase 1 of the MedSTACH project. The present deliverable is a public document and foresees to convey a concise information to all interested parties and individuals, as far as of the symposium’s outcomes concerns.
D4.8 (Conference organization)
Keywords: Conference; Symposium